Productive performance and dynamics of blood metabolites in Pelibuey lambs, fed cereals, dehydrated citrus pulp and urea - Morales, H.; Stuart, Justiniano; Gonz?lez, J.; Guti?rrez, E.; Bernal, H.; Colin, J. (Cuban Journal of Agricultural Science, 2010)
Twenty-eight Pelibuey lambs with initial liveweight of 14.9 ? 2.2 kg were used through completely randomized design with factorial fit to assess the productive performance of the animals fed high energy rations and different levels of dehydrated citrus pulp (DCP) and urea. Also, the concentration of ureic nitrogen (UN), glucose and phosphorus (P) in blood serum were measured. The determinations were performed every 14 d and the trial lasted 56 d. There were no differences (P < 0.05) for the total period in the intake of dry matter or in the daily weight increase (DWI). In the last period of 14 d, the lambs that were not fed DCP in the diet diminished (P < 0.05) the DWI in 11.5 %, when the level of urea was increased from 0.5 to 1 %. The feed conversion in the lambs fed the diets with 0 % DCP and 0.5 % urea (3.28), as well as with 10 % DCP and 1 % urea (3.33), was different (P < 0.05) compared with those fed diets containing 0 % DCP and 1 % urea (3.47), the same happens for 10 % DCP and 0.5 % urea (3.58). For the period from 42 to 56 d, there was significant (P < 0.05) effect of the interaction of the levels of urea x DCP for the variables of daily weight increase (DWI), feed conversion and protein efficiency. In the days 14 and 56, the UN was increased significantly having values of 13 and 10.3 vs 22.5 and 25.3 mg/dL in lambs fed 0.5 and 1 % urea, respectively. Likewise, in the day 28, there was significant effect (P < 0.01) of the DCP on the blood UN (11.3 vs 8.7 mg/dL), and, in the 42, there was effect (P < 0.05, 31.1 vs. 27 mg/dL de UN) on the lambs fed the diets with 0 and 10 % DCP, respectively. The concentration of blood glucose was not modified by the effect of the DCP and/or the urea. There was only effect (P < 0.05) due to the interaction DCP x urea for the day 42. It is concluded that it is possible to use the citrus pulp at 10 % with 1 % of urea in high energy rations for the feeding of growing and fattening Pelibuey lambs in pens. Key words: dehydrated citrus pulp, urea, blood metabolites, productive performance, Pelibuey lambs.